Meningkatkan Kemampuan Penjumlahan Melalui Permainan Ular Tangga Untuk Anak Tunagrahita Ringan - Siregar, Masremi; Mahdi, Arisul (Jurnal Penelitian Pendidikan Khusus, 2022)
Learning mathematics for children with special needs is very important as well as for mentally retarded children. The addition ability of mentally retarded children is due to the child's lack of understanding ability and the ineffectiveness of learning addition in class. , the problem that will be studied in this study is "Improving the Ability of Addition Through Snakes and Ladders Game for Children with Mild Mental Requirements (Classroom Action Research in Class VII at SLB Negeri Padangsidimpuan). This type of research is a type of classroom action research (CAR), the subject are initials SR, W, and IR. The study was divided into two cycles in which each cycle had four stages and a meeting place in each cycle. From the results of the study obtained the following values: initial ability SR 40%, W 50%, IR 40% then given action in the first cycle increased to SR 60%, W 65%, IR 60% then continued in the second cycle the child's ability increased to SR 90%, W 85%, IR 90%. Thus, it can be concludet that the through snakes and ladders game for mild mentally impaired children (Classroom Action Research in class VII at SLB Negeri Padangsidempuan).